LUTAS TERRITORIAIS INDÍGENAS: MEMÓRIAS, CULTURAS E EDUCAÇÕES DO POVO TUPINIKIM - Schubert, Arlete Maria Pinheiro (2021)
The research, which results from the present work, seeks to describe and analyze the process of confrontations and fronts of territorial struggles in their relationship with a cultural and ethnic re-elaboration of the Tupinikim Indigenous People, carried out in the villages of Aracruz, Espírito Santo, Brazil, between 1970 and 2010. It problematizes questions about memories, cultures and educations in their interfaces with territorial struggles, and seeks to answer questions not always present in pedagogical questions: Does indigenous struggle for land educate? Is there a properly pedagogical dimension to the actions of indigenous communities and cultures on behalf of their territorial and identity rights? The investigation processes work with participatory research (BRANDÃO, 1999), qualitative approaches in education (ANDRÉ and LÜDKE, 1986; BRANDÃO et al., 2019; FICHTNER et al., 2020) and with approaches to an implied ethnography (GEERTZ, 1989; ALBERT, 2015) and the historiographical study (LE GOFF, 1982, 2012). It benefits from immersions and observations in the villages, semi-structured interviews on the subject, notes in a field diary, as well as documentary analysis, among others. Observes the plurality of sources, oral and written, such as technical reports, government guidelines, specialized publications and/or published by indigenous, governmental and nongovernmental organizations, interviews and narratives - produced in dialogues with the protagonists of the territorial struggles of the Tupinikim Indigenous People, delimited for the present research, as well as with regional and national indigenous leaders, compared by the indicatory reading (GINZBURG, 2002, 2007). The publications on the Tupinikim Indigenous People are contextualized, including aspects of their history, culture and education, based on academic and non-academic productions accumulated on these people in the period studied. Some theoretical-methodological discussions contributed to the dialogue with indigenous and non-indigenous authors, to reflect on understandings and notions, such as: memories, cultures and educations (BENJAMIN, 2006; BRANDÃO, 2008, 2019; FREIRE, 1972; KRENAK, 1992, 2015; MUNDURUKU, 2012; RAUL MEJIA, 2012; ARROYO, 2011, 2012), in contexts of indigenous territorial struggles (OLIVEIRA, 1998; BARTOLOMÉ, 2006; QUIJANO, 2006; KRENAK, 2015; MUNDURUKU, 2012). The data produced, its treatment and analysis, lead to affirm the following thesis: memories, cultures and education constitute the inseparable bases of the territorial struggles of the Tupinikim Indigenous People and configure knowledge for the elaboration of a pedagogy against forgetfulness and its own indigenous education.